Contributions to the Study of Sociology of Education: Classical Authors - Valerie Quentin; Ficrence Sophie (Global Writing Academica Researching and Publishing, 2022)
Since its origins, sociology has focused on the study of specific areas such as education, in order to become a science that not only explores the scientific studies, but is also specialized on the subject matter. This article presents an overview of the contributions of various theoretical European traditions regarding education. From the “theoretical inputs” presented, the reflection and theoretical proposal about the subject matter related to the sociology of education are re-defined, due to a seemingly lack of clarity or consensus among the authors. Mainly, this research attempts to analyze those core issues related to the understanding of the multiple interactions between society-education and vice versa, visible from sociology. As one of the main findings, it is argued that the traditionally named sociology of education encompasses three subject matters: sociology of education, pedagogical sociology and the sociology of the educational system. Although these lines of research are intertwined, its categorization facilitates the specific understanding of various aspects within the same subject matter.